The Toyota product development system : integrating people, process, and technology - Morgan, James M. (Productivity Press, 2006)
The ability to bring new and innovative products to market rapidly is the prime critical competence for any successful consumer-driven company. All industries, especially automotive, are slashing product development lead times in the current hyper-competitive marketplace. This book is the first to thoroughly examine and analyze the truly effective product development methodology that has made Toyota the most forward-thinking company in the automotive industry. Winner of the 2007 Shingo Prize For Excellence In Manufacturing Research! In The Toyota Product Development System: Integrating People, Process, and Technology, James Morgan and Jeffrey Liker compare and contrast the world-class product development process of Toyota with that of a U.S. competitor. They use extensive examples from Toyota and the U.S. competitor to demonstrate value stream mapping as an extraordinarily powerful tool for continuous improvement. Through examples and case studies, this book illustrates specific techniques and proven practices for dealing with challenges associated with product development, such as synchronizing multiple disciplines, multiple function workload leveling, compound process variation, effective technology integration, and knowledge management. Readers of this book can focus on optimizing the entire product development value stream rather than focus on a specific tool or technology for local improvements.
Keywords: Toyota Jidōsha Kōgyō Kabushiki Kaisha.; Toyota Jidōsha Kōgyō Kabushiki Kaisha; Automobiles -- Design and construction.; Project management.; Concurrent engineering.; elektronické knihy; electronic books